Impact of confinement due to covid-19 on the emotional and behavioral state of children with disabilities - Dioses Chocano, Alejandro (2023)
The measures implemented due to COVID-19 significantly affected the life of society in general, however, diverse and differentiated effects are recognized in the population of children with disabilities, both in their emotional and behavioralwell-being. Therefore, the objective of this study was to determine the effects of home lockdown, because of COVID-19 in the year 2020, on the emotional and behavioral state of children with disabilities. For this purpose, a descriptive, nonexperimental research was implemented, with a cross-sectional non-probabilistic selective design, being the study variables, home lockdown, and the emotional and behavioral state of children with disabilities. The participants were 68 parents of children with disabilities in Special Basic Education (SBE) and Regular Basic Education (RBE) in Metropolitan Lima, selected by non-probabilistic convenience sampling. The instruments used were a sociodemographic form and an online questionnaire based on the COVID-19 and ASD Questionnaire. The results found an increase of children who decreased their speech skills, conversation initiation and voice volume; eye contact, following instructions and rules; facial expression, recognizing others’ feelings and communicating emotional states; listening to stories, sharing toys and belongings.